Aminoglycoside‐Enabled Elucidation of Bacterial Persister Metabolism. Issue 1 (2nd February 2015) - Orman, Mehmet A.; Mok, Wendy W. K.; Brynildsen, Mark P.
Abstract: Bacterial persisters are cells with an impressive, yet transient, tolerance toward extraordinary concentrations of antibiotics. Persisters are believed to impose a significant burden on the healthcare system because of their role in the proclivity of infections to relapse. During antibiotic challenge, these rare, phenotypic variants enter a dormant state where antibiotic primary targets are rendered inactive, allowing them to survive. Once the antibiotic is removed, persisters reawaken and resume growth, leading to repopulation of the environment. Metabolism plays a pivotal role in coordinating the entry, maintenance, and exit from the persister state. However, the low abundance, transient nature, and similarity of persisters to other cell types have prevented their isolation, which is needed for direct metabolic measurements. In this unit, we describe a technique known as the aminoglycoside (AG) potentiation assay, which can be used to rapidly and specifically measure the breadth of persister metabolism in heterogeneous populations. © 2015 by John Wiley & Sons, Inc.